The role of N-linked glycosylation on the structure and function of somatic angiotensin-converting enzyme - Nkoe, Karabelo M (Department of Medicine, 2015)
Angiotensin converting enzyme (ACE) is a key regulator of blood pressure and comprised of two homologous domains (N- and C-domain), both of which are glycosylated. N-linked glycosylation is important for the processing, expression and stability of ACE, but it interferes with protein crystallization. Previously, the N-glycan site occupancy required for the expression and stability of the individual domains of ACE was determined using minimally glycosylated (MG) N- and C-domain isoforms. However the role of glycosylation in the structure and function of the full-length somatic ACE (sACE) has remained elusive. A novel MG-sACE mutant, comprised of previously characterized MG N- and C-domains was generated. Unfortunately, the protein was susceptible to limited proteolysis in the interdomain linker region, suggesting that key glycans might shield the linker region from proteolysis. Furthermore, a loss in expression of MG-sACE was observed. These observations prompted the investigation of the effect of N-glycosylation on protection from inter-domain linker proteolysis, expression and overall stability of sACE. These aims were addressed by generating a panel of sACE glycosylation mutants.